Selective crossectomy combined with mechanochemical ablation in the treatment of great saphenous vein insufficiency: Early results of a single center experience. (August 2022) - Petrone, Anna; Peluso, Antonio; Ammollo, Raffaele P; Turchino, Davide; del Guercio, Luca; Andreucci, Michele; Serra, Raffaele; Bracale, Umberto M
Background: Selective crossectomy and mechanochemical ablation (MOCA) of great saphenous vein (GSV) have been used, for years, individually in the treatment of chronic venous insufficiency. In this paper, we focus on the advantages of a combination of the two techniques, in order to prevent complications and recurrence. Methods: A preoperative clinical and instrumental screening phase was conducted for the purpose of dividing patients into three groups: "Saph+Cross" group (51/139 patients) underwent saphenectomy and crossectomy; "MOCA" group (44/139 patients) underwent MOCA of GSV with Flebogrif® device; "MOCA + Cross" group (44/139 patients) subjected to both MOCA and crossectomy procedures. Recurrence rate, defined as total recanalization of GSV and/or onset of neosaphena and/or new varicose veins, was used as a primary outcome. Secondary outcomes were procedural time and intra- and post-procedural complications. Results: We conducted a 1-, 6-, and 12-month follow-up with Duplex scan. The recurrence rates were 3.9%, 21.8%, and 4.5% for "Saph+Cross, " "MOCA, " and "MOCA+Cross, " respectively, with a significant difference for the comparison between "MOCA" and "Saph+Cross" (MOCA vs Saph+Cross: OR 5.35, CI95% [0.98; 54.6], p -value .040). The sub-analysis of primary outcome highlighted a lower recanalization rate of GSV when combining the crossectomy with MOCA procedure (2.2% MOCA+Cross vs 15.9% MOCA; 0.12 OR, [0.002; 1.02] CI95%, p -value .029). Among the secondary outcomes, "MOCA" showed a shorter procedural time than the other groups (Saph+Cross: 51.3 ± 11.4; MOCA: 45.1 ± 7.5; MOCA+Cross: 50.4 ± 10; p -value .027). No significant differences were noted in terms of intra- and post-procedural complications. Conclusions: The results showed that patients treated with saphenectomy and crossectomy have a lower recurrence rate compared to MOCA alone and MOCA + crossectomy procedures. The association of crossectomy with MOCA significantly reduces the recanalization rate of GSV, and it is also characterized by a higher free survival from recurrence (SSF) than with MOCA alone.